Customer takaful management process as a finance instrument by AIA Public Takaful agents - Mohd Ali, Nursyahida (2024)
This study investigates the customer Takaful management process as a financial instrument by AIA Public Takaful, addressing the challenges faced by Takaful agents and the factors influencing client choices. The research aims to understand the management process employed by Takaful agents, analyze their roles, and identify the challenges they encounter in the Takaful landscape. Utilizing a mixed-methods approach, the study incorporates qualitative interviews with Takaful agents. Key findings reveal that effective communication and trust-building are crucial for Takaful agents in managing customer relationships. Additionally, the study identifies significant challenges such as regulatory compliance, market competition, and customer awareness of Takaful products. The implications of this research highlight the need for enhanced training and support for Takaful agents to improve service delivery and customer satisfaction. Furthermore, the findings contribute to the broader understanding of Takaful as a viable financial planning tool, emphasizing its importance in promoting financial security among clients. This research not only enriches the existing literature on Takaful management but also serves as a valuable resource for stakeholders, including Takaful companies, policymakers, and potential clients, in fostering a more informed and effective Takaful environment.